Synaldis distracta Nees 1834 ... - Gadallah, Neveen S.; Ghahari, Hassan; Peris-Felipo, Francisco Javier; Fischer, Maximilian (Zenodo, 2015)
Synaldis distracta (Nees, 1834) Distribution in Iran. Isfahan (Ghahari et al. 2011c; Khajeh et al. 2014), East of Iran (no locality cited) (Yari et al. 2014), Iran (no locality cited) (Yu et al. 2012; Peris-Felipo 2013). Distribution outside Iran. Austria, Germany and Tunisia (Francés and Jiménez 1989b; Fischer 1993b; Broad et al. 2012; Yu et al. 2012; Peris-Felipo 2013), Bulgaria, China, Croatia, Finland, Greece, Hungary, Iceland and Ireland (Francés and Jiménez 1989b; Peris-Felipo 2013), Lithuania, Madeira Islands, Mongolia, Poland, Romania, Russia, Slovenia, Sweden, Switzerland and Uzbekistan (Yu et al. 2012; Peris-Felipo 2013), Czech Republic (Lozan et al. 2010; Yu et al. 2012; Peris-Felipo 2013), Israel (Papp 2011–2012), Korea (Papp 2007b; Yu et al. 2012; Peris- Felipo 2013), Spain (Francés and Jiménez 1989b; Fischer et al. 2008; Yu et al. 2012; Peris-Felipo 2013), United Kingdom (Francés and Jiménez 1989b; Fischer 1993b; Broad et al. 2012; Yu et al. 2012; Peris-Felipo 2013), former Yugoslavia (Francés ... : Published as part of Gadallah, Neveen S., Ghahari, Hassan, Peris-Felipo, Francisco Javier & Fischer, Maximilian, 2015, An annotated catalogue of the Iranian Alysiinae (Hymenoptera: Braconidae), pp. 1-28 in Zootaxa 3974 (1) on page 8, DOI: 10.11646/zootaxa.3974.1.1, http://zenodo.org/record/288961 ...